STATISTICAL INDICATORS FOR HEALTH QUALITY MANAGEMENT - Burgio, Giuseppe (Journal of European Economy, 2017)
Measuring the performance of healthcare systems is of paramount importance for optimisation of health spending, as well as for elimination of deficiencies in the quality of care. Different statistical methods and measures of effectiveness, efficiency, responsiveness and equity of this performance are available. Several performance indicators may be used, depending on the specific field of application and on the behaviour to be changed – of providers, professional bodies, citizens, or managers. This paper provides for a critical analysis of the currently used statistical techniques and indicators, in particular those aiming at measuring hospital performance for better health quality management.